2012
DOI: 10.1134/s0031918x12020135
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of Fe2NiAl and Fe2MnAl Heusler alloys

Abstract: Results of the investigation of the optical properties and of the calculations of the electronic struc ture of Fe 2 NiAl and Fe 2 MnAl alloys are presented. The main attention is paid to the ellipsometric study of the spectral dependence of the real (ε 1 ) and imaginary (ε 2 ) parts of the dielectric constant in the range of wavelengths λ = 0.3-13 μm. An anomalous behavior of the optical conductivity σ(ω) at IR frequencies has been revealed in Fe 2 MnAl, which differs substantially from that in Fe 2 NiAl. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…However, the density of states of each pair of compounds are qualitatively similar. The highlights of the electronic structure in both Fe 2 CrAl [65] and Fe 2 MoAl are a pseudogap in the spin-up band and a gap cutting through the Fermi level in the spindown band, although in case of Fe 2 MoAl, it is more like a pseudo gap reducing its spin polarization. This difference in the electronic structure once again stems from the availability of states near and at Fermi level in case of the Fe 2 MoAl, presumably because of the hybridizations of Fe with delocalized Mo states.…”
Section: Exchange Interactions and Curie Temperaturementioning
confidence: 99%
“…However, the density of states of each pair of compounds are qualitatively similar. The highlights of the electronic structure in both Fe 2 CrAl [65] and Fe 2 MoAl are a pseudogap in the spin-up band and a gap cutting through the Fermi level in the spindown band, although in case of Fe 2 MoAl, it is more like a pseudo gap reducing its spin polarization. This difference in the electronic structure once again stems from the availability of states near and at Fermi level in case of the Fe 2 MoAl, presumably because of the hybridizations of Fe with delocalized Mo states.…”
Section: Exchange Interactions and Curie Temperaturementioning
confidence: 99%
“…7 Optical and MO properties of a number of half-metallic FHA's have been investigated theoretically and experimentally. [8][9][10][11][12][13][14][15][16][17] It has been shown that the predictions significantly depend on the calculation methods employed. 12,17 At the same time, the experimental optical and MO properties of the HA's are often quite difficult to explain without first-principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Optical properties of Ni, Co, and Fe based HA have been widely investigated theoretically and experimentally [2,[4][5][6][7][8]. The most comprehensive experimental study of various bulk HAs has been carried out by Shreder et al [9][10][11][12][13][14]. However, only a few publications have been focused on the study of the effect of structural transformations in HA on their optical properties and hence the electronic structure.…”
Section: Introductionmentioning
confidence: 99%